2013
DOI: 10.3113/jsoa.2013.0157
|View full text |Cite
|
Sign up to set email alerts
|

Knee Manipulation After Total Knee Arthroplasty: Comparison of Two Implant Designs

Abstract: Substantial postoperative stiffness requiring manipulation is a well-recognized complication of total knee replacement. This study sought to determine whether the Medial-Pivot (MP) knee (Wright Medical, Memphis, TN) or the Double-High (DH) knee (Wright Medical) is more often associated with manipulation under anesthesia (MUA) for post-total knee arthroplasty (TKA) knee stiffness. It was hypothesized that manipulation rates would be similar. Retrospective review of 755 TKA patients showed that 4.1% required MUA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…2). Its prevalence was significantly (p = 0.033) lower in studies with >24 months of follow-up 1,4,12,[16][17][18]20,28,30,31,36,38,39,44,54 (3%, I 2 = 96%) than in those with £24 months of followup 19,29,[32][33][34][35]37,40,41,43,[45][46][47][48][49][50][51]53 (4%, I 2 = 85%) (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2). Its prevalence was significantly (p = 0.033) lower in studies with >24 months of follow-up 1,4,12,[16][17][18]20,28,30,31,36,38,39,44,54 (3%, I 2 = 96%) than in those with £24 months of followup 19,29,[32][33][34][35]37,40,41,43,[45][46][47][48][49][50][51]53 (4%, I 2 = 85%) (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…In the majority (63%) of the studies, a range of motion of <90°or a flexion contracture of >5°was used to define postoperative acquired idiopathic stiffness 1,12,[17][18][19][20]28,[32][33][34][35]38,[42][43][44][45][46][48][49][50][51] . Previous studies have demonstrated that 105°to 110°is the minimum knee flexion required to perform most activities of daily living (ADLs) in Western societies such as rising from a chair, walking, and ascending stairs 55,56 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We did not investigate component positioning, as there were no open manipulations, and no component changes were found to be necessary as the surgeons did not find any gross misplacement. Also, the choice of prosthesis was at the surgeons’ discretion, and could possibly influence the prevalence of MUA, as one recent study found different prevalences associated with different types of prostheses ( Berend et al 2013 ) whereas others did not ( Barnes et al 2013 ; Peters et al 2014 ). Although 1 study found that warfarin prophylaxis (compared to LMWH) resulted in more arthrofibrosis, necessitating manipulation in 26% as opposed to 6% of patients ( Walton et al 2005 ), we did not study this aspect as none of the patients received prolonged warfarin prophylaxis ( Jørgensen et al 2013c ).…”
Section: Discussionmentioning
confidence: 99%